Studying the Granulometric Composition of Rice Dust for Solving the Issues of Improving Environment Safety - Korotkova, Tatyana Germanovna (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of this study is to determine the granulometric composition of the rice dust generated during processing rice powder at LLC â€œSouthern Rice Company (SRC),â€ which is a strong allergen, to improve the environmental safety of production and working conditions. Material and Methods: Two samples of dust detained by a group cyclone and a bag filter-cyclone installed at LLC SRC were taken (station Kholmskaya, the Krasnodar region, Russia). To define the granulometric composition of dust for the fractions between 10 and 0.5 mm, the sieve method without rinsing with water was used, for fractions <0.5 mm, the sieve method with rinsing with water was used. In using the sieve method, the average sample for the analysis was taken using the quartering method. The weight of the sample was 50 g. Results and Discussion: The analysis of the content of rice dust fractions showed that a battery cyclone removes dust particles with the size between 10 and 1 mm. The fraction between 2 and 1 mm has the greatest percentage, equal to 39.4%. A bag filter-cyclone captures 90.42% of finer rice dust with a particle size <0.5 mm, out of which 65.34% are fine particles with size <0.1 mm. Conclusion: Introduction of a bag filter-cyclone at LLC â€œSRCâ€ made it possible to increase the environmental safety of the production, to reduce overall emissions of pollutants into the atmosphere, and to improve the working conditions.